Diversity Management Study: Best Practice for “A Bank” Operating In Diversity Management - Zhang, Han (2010)
Diversity Management has become increasingly attractive in recent years. A Bank has invested in diversity programs in order to create a competitive advantage for the organization; this will enable A Bank to become more knowledgeable regarding their diverse of customer base, and make their customers feel more comfortable when dealing with organizational members. A Bank will also be able to increase productivity with regards to complex tasks, increase problem solving through knowledge resources, and support innovative strategies.